1999
DOI: 10.1007/bf02236201
|View full text |Cite
|
Sign up to set email alerts
|

Familial adenomatous polyposis

Abstract: Endoscopic eradication is an appropriate initial treatment for histologically advanced, noncancerous neoplasms or for patients who are not surgical candidates. Pancreas-sparing duodenectomy may be the treatment of choice for patients with carcinoma and those who have failed endoscopic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In patients with familial adenomatous polyposis (FAP) the management of duodenal and ampullary lesions is particularly controversial because of local recurrence. Some have suggested that repeated endoscopic therapy is a reasonable option for histologically advanced, non-cancerous lesions [7], whereas others have recommended early radical surgery [8]. The relative roles of endoscopy, local resection, and radical resection in the management of peri-ampullary lesions for FAP is still not clearly defined [9], and peri-ampullary carcinoma is now the leading cause of death in patients afflicted with this syndrome.…”
mentioning
confidence: 99%
“…In patients with familial adenomatous polyposis (FAP) the management of duodenal and ampullary lesions is particularly controversial because of local recurrence. Some have suggested that repeated endoscopic therapy is a reasonable option for histologically advanced, non-cancerous lesions [7], whereas others have recommended early radical surgery [8]. The relative roles of endoscopy, local resection, and radical resection in the management of peri-ampullary lesions for FAP is still not clearly defined [9], and peri-ampullary carcinoma is now the leading cause of death in patients afflicted with this syndrome.…”
mentioning
confidence: 99%
“…However, it is also noted that nearly 50% of patients with adenocarcinoma have not had Spigelman stage IV disease 5 . Guidelines suggest patients with advanced duodenal polyposis be considered for prophylactic duodenectomy including pancreaticoduodenectomy (PD), pancreas-sparing duodenectomy (PSD), or segmental duodenectomy (SD), which is more effective than local surgical or endoscopic polypectomy 6–8 …”
mentioning
confidence: 99%